Development of a Routine Screening Method for the Microplastic Mass Content in a Wastewater Treatment Plant Effluent - Goedecke, Caroline; Eisentraut, Paul; Altmann, Korinna; Elert, Anna Maria; Bannick, Claus G.; Ricking, Mathias; Obermaier, Nathan; Barthel, Anne-Katrin; Schmitt, Thomas; Jekel, Martin; Braun, Ulrike (Frontiers in Environmental Chemistry, 2022)
An investigation of microplastic (MP) occurrence in a municipal wastewater treatment plant (WWTP) effluent with tertiary treatment was carried out. Representative sample volumes of 1 m3 were taken by applying a fractionated filtration (500 µm, 100 µm, 50 µm mesh sizes). The detection of MP mass fractions by Thermal Extraction Desorption - Gas Chromatography / Mass Spectrometry (TED-GC/MS) was achieved without the previously required additional sample pretreatment for the first time. Different types of quantification methods for the evaluation of TED-GC/MS data were tested and their accuracy and feasibility have been proven for real samples. Polyethylene, polystyrene and polypropylene were identified in the effluent samples. The polymer mass content varied significantly between 5 mg m-3 and 50 mg m-3. A correlation between the MP load and the quantity of suspended matter in the WWTP effluents, particle size distribution, particle type, and operation day (i.e. weekday, season, capacity) was not found. No correlation was found between the MP load and suspended matter in the WWTP effluents, as well as particle size distribution, particle type or operation day (i.e. weekday, season, capacity). It can be concluded, that the meaningful assessment of WWTPs requires a comprehensive sampling campaign with varied operation conditions.